Pengaruh Kepemimpinan Transformasional, Komunikasi, Dan Komitmen Organisasional Terhadap Kinerja Sukarelawan Pengurus UKM Jam’iyyatul Qurro’ Wal Huffadz Unisma - Andriyani, Fita; Nurhidayah, Nurhidayah; Amin, Muhammad Sirojuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to determine the influence of Transformational Leadership, Communication, and Organizational Commitment on the Performance of UNISMA Jam'iyyatul Rurro' Wal Huffadz (JQH) Management Volunteers. This type of research is a quantitative research, namely research in the form of numbers and analysis using statistics The population in this study is the entire management of UKM JQH UNISMA and with the number of samples obtained by 49 students using saturated sample techniques. Data was collected using questionnaires  through google form  and and analyzed by multiple linear regression through Statistical Program Social Science (SPSS) version 25. The results of this study show that transformational leadership, communication and organizational commitment have a significant effect on the performance of volunteers in the management of UKM JQH UNISMA Keywords : Leadership, Communication, Commitment, Volunteer Performance, Management